2014
DOI: 10.1039/c4ra02394c
|View full text |Cite
|
Sign up to set email alerts
|

Regio-selective synthesis of polyepichlorohydrin diol using Zn–Co(iii) double metal cyanide complex

Abstract: This work describes the first regio-selective synthesis of poly(epichlorohydrin) diol via a simple one-pot bulk polymerization with a heterogeneous catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Remarkably, the cyclic carbonate contents in the product were 5.0%-11.3% at 25-60 o C, better than those from homogeneous catalysis [141]. Moreover, the copolymer with 70.7% carbonate content presents high thermal decomposition temperature of 250 o C and relatively high T g of 31.2 o C. Although we observed that Zn-Co(III) DMCC was a regioselective catalyst for ROP of epichlorohydrin on the site of methine group [142], we had no direct evidence for supporting the regioselective CO 2 /epichlorohydrin copolymerization. Terpolymerization of two epoxides with CO 2 could also performed well by Zn-Co(III) DMCC catalyst, affording terpolymers with tunable T g s [143].…”
Section: Structural Effect Of Epoxides On Co 2 /Epoxide Copolymerizationmentioning
confidence: 70%
“…Remarkably, the cyclic carbonate contents in the product were 5.0%-11.3% at 25-60 o C, better than those from homogeneous catalysis [141]. Moreover, the copolymer with 70.7% carbonate content presents high thermal decomposition temperature of 250 o C and relatively high T g of 31.2 o C. Although we observed that Zn-Co(III) DMCC was a regioselective catalyst for ROP of epichlorohydrin on the site of methine group [142], we had no direct evidence for supporting the regioselective CO 2 /epichlorohydrin copolymerization. Terpolymerization of two epoxides with CO 2 could also performed well by Zn-Co(III) DMCC catalyst, affording terpolymers with tunable T g s [143].…”
Section: Structural Effect Of Epoxides On Co 2 /Epoxide Copolymerizationmentioning
confidence: 70%
“…DMC is a heterogeneous catalyst with the general structure of M 1 u [M 2 (CN) 6 ] v · x M 1 X w · y L· z H 2 O, where M 1 = Zn, M 2 = Co, Fe. L is an organic complexing agent, such as tert -butyl alcohol, diglyme, or other. , A proposed structure of the DMC catalyst is shown in Scheme …”
Section: Polymerization Of Alkylene Oxides: Methodsmentioning
confidence: 99%
“… a Here, the Zn–OH structure acts as the initiating group. L represents a complexing agent, used during the preparation of the catalyst, e.g., tert -butanol …”
Section: Polymerization Of Alkylene Oxides: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of the possibility of preparing high molar mass and often stereoregular (co)­polymers of ECH, catalytic ROP of ECH suffers from some difficulties in controlling the molar mass and chain-end functionality. Also, in some instances, incomplete monomer conversion was observed. ,, The catalytic regioselective polymerization of ECH using a Zn-Co­(III) double metal cyanide complex, which favors formation predominantly of PECH diols, albeit low molar masses ( M n < 3500 g mol –1 ) and relatively high dispersity (Đ > 1.5) with semi-crystalline properties (solid–liquid transition around 100 °C), was reported recently …”
Section: Introductionmentioning
confidence: 96%